PENGARUH PEMBERIAN EKSTRAK KULIT PISANG KEPOK (Musa acuminata) TERHADAP GAMBARAN HISTOPATOLOGI BRONKUS DAN VENA PULMONALIS MENCIT (Mus musculus) JANTAN YANG DIPAPAR ASAP ROKOK - Jeanita, Winny; Meles, Dewa Ketut; WIdjiati, Widjiati; Hamid, Iwan Sahrial; Luqman, Epy Muhammad; Arimbi, Arimbi (Universitas Airlangga, 2020)
This research aimed to attest the effect of Kepok banana (Musa acuminata) peel extract on the histopathology of bronchus and pulmonary veins in male mice (Mus musculus) exposed by cigarette smoke. The 24 experimental male mice were divided into six groups with each treatment having four replicate. All the groups, except K- as a control group, was treated with cigarette smoke for 14 days. After that, K- and K+ was treated with CMC-Na 1%, KO was treated with ascorbic acid 13 mg/kgBW, P1 was treated with Kepok banana peel extract 14 mg/kgBW, P2 was treated with Kepok banana peel extract 28 mg/kgBW, and P3 was treated with Kepok banana peel extract 56 mg/kgBW for 14 days. The data of the thickness of bronchial epithelium and the diameter of pulmonary veins were analyzed using ANOVA (Analysis of Varience) with significance p<0,05 and continued with Post- hoc Tukey. The result of the thickness of bronchial epithelium showed that K+ had the highest thickening (431,83 + 9,71 µm) and significant differences (P<0,05) with all the groups. The result of P3 showed the lowest thickening of bronchial epithelium (170,84 + 2,70 µm). The result of pulmonary veins diameter showed that K+ had the narrowest diameter (525,64 + 16,61 µm) and significant differences (p<0,05) with all the groups. The result of P3 showed the lowest diameter narrowing of pulmonary veins (718,10 + 9,64 µm). The conclussion of this research are Kepok banana peel extract able to decreased the thickness of bronchial epithelium and the narrowing of pulmonary veins diameter in male mice with effective dose 28 mg/ kgBW.